Considerații cu privire la regimul juridic al terenurilor în lumina dreptului Uniunii Europene // Considerations regarding the legal regime of the land in the light of European Union law - Elena Sârghi (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2023)
This article analyses the legal regime of land adopted by the Romania and other member states by reference to European legal norms. In this sense, the paper is divided into three parts. The first part is intended for the national legal framework, in the form of a chronological axis before and after the accession at the European Union. The second part is reserved for Union law, by analysing the regulations and the jurisprudence of the Court of Justice of the European Union, in order to observe how the organization's policies regarding free movement should be carried out and how this normative framework is interpreted. The last part is structured in the form of benchmarks of comparative constitutional law of the member states and the ways the Union acts in order to improve the restrictive regime adopted by the states regarding the free movement of land.